APPROXIMATE METHOD ANALYSIS OF THERMAL ELECTROMAGNETIC BALLASTS FOR DISCHARGE LAMPS - , К. К. (Municipal economy of cities. Series: «Economy science», 2013)
A brief analysis of the simplified method of thermal regime of the ballast choke kits "RL - Ballast," which can be used in the practice of engineering in the design.